1985
DOI: 10.1126/science.3838821
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Distribution of Brain Dopamine Receptors Evidenced with [ 125 I]Iodosulpride, a Highly Selective Ligand

Abstract: The new benzamide derivative [125I]iodosulpride is a highly sensitive and selective ligand for D-2 dopamine receptors and displays a very low nonspecific binding to membrane or autoradiographic sections. On autoradiographic images, D-2 receptors are present not only in well-established dopaminergic areas but also, in a discrete manner, in a number of catecholaminergic regions in which the dopaminergic innervation is still unknown, imprecise, or controversial, as in the sensorimotor cerebral cortex or cerebellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
83
1
4

Year Published

1988
1988
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(100 citation statements)
references
References 31 publications
12
83
1
4
Order By: Relevance
“…These observations are in good agreement with the rostro-caudal gradient known for the cortical distribution of dopamine concentrations (Kehr et al 1976), dopaminergic terminals (Descarries et al 1987) and DA-receptors (Martres et al 1985;Dawson et al 1986a;Dawson et al 1986b). …”
Section: Dopaminergic Projections From Midbrain To Nacsupporting
confidence: 88%
“…These observations are in good agreement with the rostro-caudal gradient known for the cortical distribution of dopamine concentrations (Kehr et al 1976), dopaminergic terminals (Descarries et al 1987) and DA-receptors (Martres et al 1985;Dawson et al 1986a;Dawson et al 1986b). …”
Section: Dopaminergic Projections From Midbrain To Nacsupporting
confidence: 88%
“…As F rac cannot be measured directly, this is estimated from the count rate density (i.e., F rac plus nonspecific binding) in the cerebellum, a brain region almost devoid of D 2 R (Martres et al 1985). However, in vivo the endogenous DA competes with [ 11 C]raclopride for the D 2 R. This competition can be represented as:…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Because it has been demonstrated that the con centration of dopamine D2 receptors is negligible in cerebellar tissue (Kuhar et al, 1978;Martres et al, 1985), the cerebellum data have been fitted using the model shown in Fig. 1 without specific binding and thus including only four parameters.…”
Section: Parameter Identificationmentioning
confidence: 99%